2021
DOI: 10.3390/rs13112102
|View full text |Cite
|
Sign up to set email alerts
|

Integration of L-Band Derived Soil Roughness into a Bare Soil Moisture Retrieval Approach from C-Band SAR Data

Abstract: Surface soil moisture (SSM) is a key variable for many environmental studies, including hydrology and agriculture. Synthetic aperture radar (SAR) data in the C-band are widely used nowadays to estimate SSM since the Sentinel-1 provides free-of-charge C-band SAR images at high spatial resolution with high revisit time, whereas the use of L-band is limited due to the low data availability. In this context, the main objective of this paper is to develop an operational approach for SSM estimation that mainly uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…With the objective of simplifying the parameterization of the retrieval models the use of the proposed σ D (NDVI) allowed to integrate vegetation effects in the roughness parameter, as previously suggested by Capodici et al [52]. Note that, recently, Hamze et al [92] estimated soil roughness from L-band images, improving significantly soil moisture mapping derived using C-band SAR data. In addition, El Hajj et al [93] demonstrated that the use of L-band images can be attractive for high NDVI (>0.7) in several crops, overcoming the limitations of C-band.…”
Section: Soil Moisture Estimation From Radar Satellite Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the objective of simplifying the parameterization of the retrieval models the use of the proposed σ D (NDVI) allowed to integrate vegetation effects in the roughness parameter, as previously suggested by Capodici et al [52]. Note that, recently, Hamze et al [92] estimated soil roughness from L-band images, improving significantly soil moisture mapping derived using C-band SAR data. In addition, El Hajj et al [93] demonstrated that the use of L-band images can be attractive for high NDVI (>0.7) in several crops, overcoming the limitations of C-band.…”
Section: Soil Moisture Estimation From Radar Satellite Observationsmentioning
confidence: 99%
“…In addition, El Hajj et al [93] demonstrated that the use of L-band images can be attractive for high NDVI (>0.7) in several crops, overcoming the limitations of C-band. Nowadays, L-band images are not available with high revisit time, in contrast with the C-band images of Sentinel 1, and, therefore, are not appropriate for operational soil moisture mapping [92]. In the next future, L-band images should be available at higher revisit time with the new SAR missions (e.g., NISAR (NASA-ISRO SAR), and Tandem-L; [92]), becoming attractive for operational approaches.…”
Section: Soil Moisture Estimation From Radar Satellite Observationsmentioning
confidence: 99%
“…SAR data has been recently exploited to detect irrigation events, especially with the availability of the free and open-access C-band SAR images offered by the Sentinel-1 (S1) constellation. The SAR backscattering signal is known to be sensitive to the soil water content [15][16][17][18][19][20], which makes it possible to detect the wetness information of the soil following an irrigation episode. The increase in the soil moisture caused by an irrigation episode is the key element that links the use of SAR data for irrigation mapping and the detection of irrigation events.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the soil moisture within a homogenous vegetation context, several techniques have been employed to invert models, including direct inversion [44,49], change detection [29,60,61], Bayesian approaches [62], look-up tables [49,52] and artificial neural networks (ANNs) [23,[63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%